Kronopoetik dan Memori: Bagaimana Media Mengkonstruksi Pengalaman Temporal Manusia? - Dwipa, Fajar Dwi Putra (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
The presence of media provides the right time point, but without realizing it, media can reveal itself as a form of extension of protection and retention technology. The voice of civilization is systematically brought into the virtual circle so that it gives rise to assumptions and illusions that can be handled through Chronopoetic analysis. Thus, sharing the characteristics of social media users with temporal time becomes an issue that deserves to be raised in scientific studies. This study aims to identify the mechanism of media in constructing human temporal time. The method used is qualitative with an interpretive paradigm. The research findings say the existence of time subjectivity in the five subjects, the concept of newness was found in the five subjects, the existence of time dilation in three subjects, and the existence of doom-scrolling in all research subjects.